The moral sense and social environment in the construction of the personality of an inquirer: Alonso de Salazar y Frías - Lavado Suárez, Laura (Huarte de San Juan. Geografía e Historia, 2010)
This article attempts to bring us closer to the figure of the inquisitor Alonso de Salazar y Frías, the famous “witch lawyer”, through the factors which influenced the shaping of his personality. Through preserved documents relating to him we can see how his academic training, social environment, the encounters and misunderstandings with his colleagues in the courts and the disputes in the twilight of his life were elements which shaped his personality and his identity.